COMPREHENSIVE WOMEN’S HEALTH CARE IN PRIMARY HEALTH CARE: CONCEPTUAL FOUNDATIONS, ORGANIZATIONAL CHALLENGES, AND IMPLICATIONS FOR THE BRAZILIAN UNIFIED HEALTH SYSTEM (REMUNOM, 2026)
Primary Health Care (PHC) plays a strategic role in the organization of health systems guided by universality, comprehensiveness, equity, and continuity of care. In women’s health, its relevance goes far beyond reproductive assistance, encompassing health promotion, disease prevention, early detection, longitudinal management of chronic conditions, mental health care, response to violence, and intersectoral action toward social vulnerabilities. This study aimed to critically analyze the role of PHC as a structuring axis for comprehensive women’s health care within the Brazilian Unified Health System. This is a narrative literature review with a qualitative approach, based on indexed scientific publications and recent institutional documents. The findings indicate that PHC, when organized according to its essential and derived attributes, favors care coordination, broader access, bonding, longitudinality, and more effective responses to women’s health needs throughout the life course. However, important challenges remain, including fragmented care, limited incorporation of health promotion activities, weaknesses in caring for women in situations of violence, and territorial inequalities in service provision and quality. It is concluded that strengthening PHC, together with workforce qualification, use of epidemiological data, community health worker engagement, and intersectoral network consolidation, is essential for the effective implementation of comprehensive women’s health care.